Transformation in Students’ Attitude after Classroom-Based Assessment’s (PBD) Implementation on Arabic Language Subject - Satar, Hafilah Abd; Nik Yusoff, Nik Mohd Rahimi; Hamzah, Mohd Isa (International Journal of Psychosocial Rehabilitation, 2020)
Classroom-Based Assessment (PBD) is a form of a constant assessment carried out in conjunction with teaching and learning to enhance student mastery and teacher teaching. This research was administered to explore the changing nature of student attitudes towards Arabic language skills as a result of the implementation of PBD attended among lower secondary students. The design of this case study utilised comprehensive interview instruments among seven Arabic language teachers and group interviews with students who received formative assessments of Arabic language subject. Interview participants were selected with purposive sampling method who are also head coaches (JU) of PBD for the national Arabic Language for five states in Malaysia. The perfect interview data in the transcript was subsequently analysed to generate themes and subthemes employing the help of Nvivo software 12. The findings revealed that there had been a positive change in student attitude as a result of the planned implementation of the planned Arabic Language PBD. The results established that students are more active in learning activities, more competitive with peers, more aware of an Arabic language assignment, more interested in and learning Arabic, better prepared to learn Arabic language and students more confident in speaking the Arabic language with friends and teachers. Principally, the conclusions revealed that the planned implementation of PBD could attract students’ interest to Arabic language learning and promote active student engagement especially for the learning of four skills in the Arabic language among lower secondary school students.